Implication of corona formation in a metatroctolite to the granulite facies overprint of HP–UHP rocks in the Moldanubian Zone (Bohemian Massif). (2nd February 2015) - Faryad, S. W.; Kachlík, V.; Sláma, J.; Hoinkes, G.
Abstract Corona and inclusion textures of a metatroctolite at the contact between felsic granulite and migmatites of the Gföhl Unit from the Moldanubian Zone provide evidence of the magmatic and metamorphic evolution of the rocks. Numerous diopside inclusions (1–10 μm, maximum 20 μm in size) in plagioclase of anorthite composition represent primary magmatic textures. Triple junctions between the plagioclase grains in the matrix are occupied by amphibole, probably pseudomorphs after clinopyroxene. The coronae consist of a core of orthopyroxene, with two or three zones (layers); the innermost is characterized by calcic amphibole with minor spinel and relicts of clinopyroxene, the next zone consists of symplectite of amphibole with spinel, sapphirine and accessory corundum, and the outermost is formed by garnet and amphibole with relicts of spinel. The orthopyroxene forms a monomineralic aggregate that may contain a cluster of serpentine in the core, suggesting its formation after olivine. Based on mineral textures and thermobarometric calculations, the troctolite crystallized in the middle to lower crust and the coronae were formed during three different metamorphic stages. The first stage relates to a subsolidus reaction between olivine and anorthite to form orthopyroxene. The second stage involving amphibole formation suggests the presence of a fluid that resulted in the replacement of igneous orthopyroxene and governed the reaction orthopyroxene + anorthite = amphibole + spinel. The last stage of corona formation with amphibole + spinel + sapphirine indicates granulite facies conditions. Garnet enclosing spinel, and its occurrence along the rim of the coronae in contact with anorthite, suggests that its formation occurred either during cooling or both cooling and compression but still at granulite facies conditions. The zircon U–Pb data indicate Variscan ages for both the troctolite crystallization (c. 360 Ma) and corona formation during granulite facies metamorphism (c. 340 Ma) in the Gföhl Unit. The intrusion of troctolite and other Variscan mafic and ultramafic rocks is interpreted as a potential heat source for amphibolite–granulite facies metamorphism that led to partial re‐equilibration of earlier high‐ to ultrahigh‐P metamorphic rocks in the Moldanubian Zone. These petrological and geochronological data constrain the formation of HP–UHP rocks and arc‐related plutonic complex to westward subduction of the Moldanubian plate during the Variscan orogeny. After exhumation to lower and/or middle crust, the HP–UHP rocks underwent heating due to intrusion of mafic and ultramafic magma that was generated by slab breakoff and mantle upwelling.